The grease formulation using waste substances from palm oil refinery and other industrial wastes : A review - Muhammad Auni, Mauliduni; Mohd Aizudin, Abd Aziz; Nur Amira Fatihah, Bashari; Mohd Azmir, Arifin; Nedumaran, Navinash; Khairuddin, Md Isa; Umi Fazara, Md Ali (Universiti Putra Malaysia, 2023)
Many applications use Spent Bleaching Earth (SBE) despite being considered hazardous waste from the palm oil refinery process. Its production increases yearly, similar to waste cooking oil (WCO). The SBE is known as a thickener in grease formulation. The same goes for red gypsum, waste motor oil, stearic acid, and lithium hydroxide monohydrate. They are all considered thickeners but have different durability in protecting base oil in grease. Then, previous studies revealed their performances with side effects detection against the environment and human bodies. Cooking oil is a heat transfer medium for serving foods with higher amounts of unsaturated fatty acids. The number of fatty acids might change after cooking oil consumption and become highly demanded due to the chemical properties of density, viscosity and fatty acids. Nowadays, people lack awareness of the importance of recycling palm oil waste. They intend to dispose of it instead of recycling it for sustainable energy resources. Therefore, this paper will discuss the grease formulation, contaminant available in WCO, its treatment, issues regarding different thickener consumption, treatment against Spent Bleaching Earth (SBE), and propose the safe thickener and additives for future intakes. This study found that adding Fume Silica (F.S.) as a thickener and Molybdenum Disulfide (MoS2) enhanced the grease stability. Further treatment against SBE (remove residue oil) and WCO (metal elements, undesired impurities and water content) is necessary for providing good quality formulated grease.